Managing external risk factors on oil and gas project success: a dream for all firms - Adeleke, A. Q.; Ajibike, Waliu Adeniyi; Muuka, Gerry Nkombo; Mohd Ridzuan, Darun; Moshood, Taofeeq Durojaye (ASCE, 2021)
Embedded in the Malaysian oil and gas sectors’ experience, this study assesses the impact of external risk factors, which include political, economic, social, and environmental risk factors, and government support on the success of oil and gas construction projects in Malaysia using 61 employees of the oil and gas firms using a questionnaire survey. Structural equation modeling (SEM) results revealed that all the exogenous variables (political risk, economic risk, social risk, and environmental risk factors as well as government support) have a significant positive effect on project success. SEM results show that government support has no significant moderating effect on the impact of political, economic, social, and environmental risk factors on project success. The study developed an all-inclusive framework that can assist stakeholders in the sector in mitigating external risk factors in ensuring the success of projects. Policy implications and future study directions are also considered.